Analysis Of Accident Prone Areas Along Jenderal Ahmad Yani Road In Bekasi - Dermawan, Widodo Budi; Isradi, Muhammad; Pawaztris, Pawaztris (Yayasan Ahmar Cendekia Indonesia, 2019)
Based on the results of the analysis of accident prone locations on Jenderal Ahmad Yani road in 2015-2018 using the Equivalent Accident Number (EAN) method, the location that are identified as accident prone is at coordinates 6.2444641- -6.2356937 (crossing area of the Jenderal Ahmad Yani road with the Burang Rang Raya road – Overpass that leads to the Summarecon Bekasi iconic roundabout), with as many as 40 accidents. The number of death caused by traffic accident are as many as 13 people, seriously injured as many as 7 people, minor injuries as many as 46 people, and experience material loss of 37 objects and a maximum of Rp 80.800.000.- . The most dominant cause of accidents on Ahmad Yani road Bekasi in 2015-2018 is human error with 74% percentage and 26% due to vehicle error with total of 40 accidents.